Achieving Energy Efficiency in Buildings through Retrofitting Strategy: A Literature Review - Sumarno; RA Retno Hastijanti; Darmansjah Tjahja Prakasa (International Conference of Innovation and Community Engagement, 2024)
Office buildings constructed in the 2000s often face significant challenges in achieving energy efficiency, as they were not designed to adapt to modern climate conditions. This limitation leads to high energy consumption, reduced functionality, and performance degradation over time. Addressing these issues requires the implementation of retrofit strategies to improve energy efficiency, space comfort, and building resilience. This study focuses on analyzing existing research to identify effective retrofitting approaches for enhancing energy performance in office buildings. The study emphasizes passive strategies such as shading, double-skin facades, green roofs, and the use of environmentally friendly technologies and materials for building envelope modifications. Utilizing a literature review method, data were gathered from 90 research articles on retrofit strategies for existing buildings. The findings demonstrate that building envelope retrofits can significantly reduce energy consumption, improve occupant comfort, and enhance overall performance. Additionally, these strategies contribute to lowering carbon emissions, supporting a low-carbon economy, and reducing operational energy costs, making them essential for sustainable building practices.